The shaken and the stirred : the year's work in cocktail culture - Schneider, Stephen; Owens, Craig N. (Year's work (Bloomington, Ind.), 2020)
"Over the past decade, the popularity of cocktails has returned with gusto. Amateur and professional mixologists alike have set about recovering not just the craft of the cocktail, but also its history, philosophy, and culture. The Shaken and the Stirred features essays written by distillers, bartenders and amateur mixologists, as well as scholars, all examining the so-called 'Cocktail Revival' and cocktail culture. Why has the cocktail returned with such force? Why has the cocktail always acted as a cultural indicator of class, race, sexuality and politics in both the real and the fictional world? Why has the cocktail revival produced a host of professional organizations, blogs, and conferences devoted to examining and reviving both the drinks and habits of these earlier cultures?"--